Bactérias endofíticas isoladas de Caryocar brasiliense: atividade enzimática, antimicrobiana, leishmanicida e co-cultura com microrganismos patogênicos - Assis, Pamela Carla Pereira de (Universidade Federal de São Carlos, 2018)
Endophytic microorganisms are defined as those that can be isolated from healthy plant tissues, superficially disinfected and which do not cause apparent damage to the host. These microorganisms indirectly benefit the growth of plants through the production of secondary bioactive metabolites, which prevent the growth and activity of pathogenic organisms through their insecticidal and antimicrobial properties. Therefore, they are an invaluable source for the prospection of new molecules of biotechnological interest. Currently, the enzyme market has moved thousands of dollars annually, with emphasis on the enzymes produced by microorganisms. In addition, the increase of resistance to antibiotics by strain of pathogenic microorganisms has made urgent the need to develop new molecules with antimicrobial and antiparasitic activity. Hence, the aim of this study was to prospect for endophytes associated with Caryocar brasiliense, a plant species native to the Brazilian savannah. Although it is commonly used in folk medicine, there is only few studies about its endophytic community and production of secondary metabolites. Forty-two endophytic microorganisms were isolated from C. brasiliense, one was identified as an actinobacteria belonging to the genus Streptomyces. The evaluation of the enzymatic activity showed that 33.3%, 40,1%, 28,6% and 9,5% were positive for amylase, cellulase, 28.6% protease, lipase and esterase, respectively. In the preliminary tests for evaluation of antimicrobial activity, six isolates showed activity against Staphyloccocus aureus and one isolate, the actinobacteria, showed activity against Candida albicans, and was selected for the subsequent tests. Analysis of the growth kinetics of Streptomyces spp. demonstrated that the beginning of the production of bioactive substances against C. albicans started in 40 hours. The bioactivity evaluation of the crude extract produced during co-culture with potentially pathogenic microorganisms demonstrated a 50% increase in inhibition of C. albicans and promoted inhibition of S. aureus, which had not been reported in axenic culture. The microdilution assay evaluated the bioactivity of lyophilized crude extract agains C. albicans, which demonstrated an inhibition rate higher than 90% at concentration 10 mg.mL-1 and 56% at 2 mg.mL-1. The leishmanicidal effect of this extract was also observed, and the results showed cell death rate of 93% at 10 mg.mL-1.
Keywords: Co-cultivo; Antimicrobiano; Pequizeiro; Endófito; Leishmaniose; Endophyte; Co-culture; Antimicrobial; Leishmaniasis; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA